CONCEPT OF ISLAMIC EDUCATION PSYCHOLOGY IN IHYA’ ‘ULUM AL-DIN BY AL-GHAZALI - Khairina Siregar (Sekolah Tinggi Agama Islam Al Hidayah, 2020)
The concept of Islamic education psychology in Al-Ghazali's Ihya' 'ulum al-din is a tazkiyah an-Nafs effort that is taken through learning. This study aims to analyze the concept of Islamic education psychology in the book Ihya' 'ulum al-din through modern educational psychology theories and the impact of their application on the psychology of Islamic education today. This research uses a qualitative approach with a literature study method. Analysis, data sources and testing the validity of research data through reference materials (scientific). The results of this study indicate that the results of this study indicate that (1) the psychological concept of Islamic education contained in the book Ihya 'Ulum al-Din hints at the integrity and balance between science, educators and students as potential